PILIHAN HUKUM DALAM PERJANJIAN LISENSI DI BIDANG MEREK DAGANG ANTARA PARA PELAKU USAHA YANG BERBEDA KEWARGANEGARAAN BERDASARKAN UNDANGUNDANG NO.15 TAHUN 2001 TENTANG MEREK - Bob Nugraha, Nyoman; Ketut Dunia, Ngakan; Sandhi Sudarsana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
Background research based on the provision of the law as result of the licenseagreement. Because the license agreement between the different business associatescitizenship is does not always go according to agrrement.Purpose of the study is to know and understand the trademarks and licensesunder the law and determine your legal options in the event of a dispute betweenbusiness partner license agreement between different nationality.Writing researchmethod is normative legal research base on secondary dataConclusion of the study is about trademark and licenses as well as determiningthe choice of law of a license agreement case of business partner with differentnationality.
Keywords: trademark, license, nationality, law